Cartographie interactive historique pour informer sur les risques : application avec le DICRIM de la Ville de Saint-Étienne - Élisabeth Chesneau; Adeline Clément; Éric Lieghio (Développement Durable et Territoires)
A French municipality which is subject to major risks such as floods has to create a Document d'Information Communal sur les Risques Majeurs (DICRIM) for its inhabitants. This document shall include description of historical events which took place in the municipality. The map is a major tool to locate this type of information in space. In 2011, the City of Saint-Étienne, the Institute of Major Risks of Grenoble (IRMa) and the ISTHME research laboratory of the University of Saint-Étienne (UMR EVS) developed an interactive map about the historical disasters in Saint-Étienne. Within a research project, we carry out a survey to assess how the map is perceived and understood. According to the results we obtained, we create a new map by adding a timeline. A second survey allows gathering new suggestions to improve the map.